STRUCTURAL BARRIER IN THE PROCESS OF REGENERATION OF THE PKB ISLAMIC POLITICAL PARTY IN DIRECT PRESIDENTIAL ELECTIONS 2004-2019 - Nastain, M; Abdullah, Irwan; Qodir, Zuly; Jubba, Hasse (JWP (Jurnal Wacana Politik), 2024)
The purpose of this research is to identify the structural barriers faced by the PKB political party in promoting its members as presidential and vice-presidential candidates from 2004 to 2019. Additionally, the research aims to explore the political strategies employed by the PKB that resulted in the absence of its members in the highest democratic contests. Structural policies play a crucial role in determining political steps, taking into consideration both internal and external conditions. This research employs a qualitative descriptive method, combining data from interviews and documents, supported by field observations. Interview data serves as preliminary findings guiding the discovery of document data, which is further elaborated through observations. The findings indicate that the absence of PKB members in presidential and vice-presidential contests is directly attributed to a strategic decision made in 2008 to consolidate internal party divisions. The logical reasons behind PKB’s political strategy include strengthening the party’s financial stability and choosing to remain within the power circle. The ingenuity of PKB’s elite in addressing structural obstacles and turning them into a political opportunity by consolidating internal cadre and rebuilding relationships with grassroots stakeholders.